Manajemen Kesiswaan Dalam Peningkatan Kegiatan Ekstrakurikuler Pramuka - Irwandi; Muhammad Al-Fatih (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
The management of extracurricular activities, particularly Scouting, plays a vital role in shaping students’ character, discipline, and sense of responsibility. To ensure optimal and sustainable implementation, a structured and systematic student management system is required within the formal educational environment. This study aims to explore how student management is implemented at MTsN 17 Jombang, how Scouting activities are carried out, and their contribution to improving the quality of Scouting extracurricular programs. This research employs a qualitative approach with a case study method. Data collection techniques include observation, interviews, and documentation. The data were analyzed through the processes of reduction, presentation, and conclusion drawing, with data validity ensured through source, time, and technique triangulation. The findings indicate that student management plays a strategic role in the planning, organizing, implementation, and evaluation of Scouting activities. Consistent and well-directed implementation results in activities that are both beneficial and enjoyable, and positively contribute to students’ character development. The success of these activities is supported by several factors, including the support of the principal, Scout leaders, availability of facilities, and student motivation. Effective student management has been proven to enhance the quality of extracurricular activities and support the achievement of character education goals.